Biodiversity conservation :whose resource? whose knowledge? / (Acc: 1371) whose resource? whose knowledge? - Shiva, Vandana; Indian National Trust for Art and Cultural Heritage (New Delhi : Indian National Trust for Art and Cultural Heritage, 1994)
Papers presented to the INTACH Seminar on Biodiversity Conservation, People's Knowledge, and Intellectual Property Rights held on 7-8 November 1994, New Delhi, India.
Keywords: Biodiversity conservation; Right of property